An introduction to PIWI-interacting RNAs (piRNAs) in the context of metazoan small RNA silencing pathways - Astrid D. Haase (RNA Biology, 2022)
PIWI proteins and their associated PIWI-interacting RNAs (piRNAs) constitute a small RNA-based adaptive immune system that restricts the deleterious activity of mobile genetic elements to protect genome integrity. Self/nonself discrimination is at the very core of successful defence and relies on complementary base-pairing in RNA-guided immunity. How the millions of piRNA sequences faithfully discriminate between self and nonself and how they adapt to novel genomic invaders remain key outstanding questions in genome biology. This review aims to introduce principles of piRNA silencing in the context of metazoan small RNA pathways. A distinct feature of piRNAs is their origin from single-stranded instead of double-stranded RNA precursors, and piRNAs require a unique set of processing factors. Novel nucleases, helicases and RNA binding proteins have been identified in piRNA biology, and while we are starting to understand some mechanisms of piRNA biogenesis and function, this diverse and prolific class of small RNAs remains full of surprises.